The Current and Future State of the Indian Pharmaceuticals Industry - Osman Kassam, Mohamed Zahir (2010)
India’s pharmaceuticals industry is growing at a very fast pace. At present, this industry is the second largest growing industry within India, and in terms of size, it is the third largest in the world, crossing the US$20 billion threshold by the year 2015. Having said so, the industry is also currently in a transition phase from process re-engineering (duplication of patented generic drugs) to new product research and development. This paper examines the current state of the industry as well as key future trends. Strengths and weaknesses of the industry are outlined, and potential risks to the industry are identified as well.